2010
DOI: 10.1038/ajg.2010.91
|View full text |Cite
|
Sign up to set email alerts
|

Just How “Difficult” Is It to Withdraw PPI Treatment?

Abstract: Two recent studies -one of which is published in this edition of the American Journal of Gastroenterology -have reported that new dyspeptic or refl ux symptoms may develop among previously asymptomatic individuals after withdrawal of a short course of a proton pump inhibitor (PPI). It has been suggested that this is attributable to rebound gastric acid hypersecretion, and that the same phenomenon explains why some patients become chronic PPI users and physicians experience " diffi culty " in withdrawing PPI tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the case of non-erosive reflux disease it means coupling PPI therapy with weight management and lifestyle modification with the ultimate goal of tapering PPI therapy to the lowest effective dose. Prior relevant studies have shown that PPI dosage can be successfully reduced in the majority of such patients and entirely discontinued in nearly 20% [ 2 ].…”
Section: Use Of Ppismentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of non-erosive reflux disease it means coupling PPI therapy with weight management and lifestyle modification with the ultimate goal of tapering PPI therapy to the lowest effective dose. Prior relevant studies have shown that PPI dosage can be successfully reduced in the majority of such patients and entirely discontinued in nearly 20% [ 2 ].…”
Section: Use Of Ppismentioning
confidence: 99%
“…Initially developed as a treatment for reflux esophagitis, these potent inhibitors of gastric acid secretion have subsequently proven effective for a broad range of syndromes known (or suspected) to be attributable to acid reflux, acid secretion, or acid hypersecretion. Combined with seemingly excellent safety and tolerance, these broadened indications triggered an exponential increase in PPI use (and consequently cost) worldwide [ 1 , 2 ]. Furthermore, PPIs have become a victim of their own success.…”
Section: Introductionmentioning
confidence: 99%
“…PPI‐induced hypomagnesaemia occurs after prolonged PPI use, resolves within days following interruption, but resumption of treatment inevitably results in recurrence . Nevertheless, many patients are dependent on PPIs since they do not respond sufficiently to histamine‐2 receptor antagonists …”
Section: Introductionmentioning
confidence: 99%
“…Whether this was really attributable to a rebound of gastric acid hypersecretion remains to be elucidated. Although there is no direct evidence that such an effect is relevant to the GERD population, it is probably wise to use PPIs at the lowest effective dose [24] and progressively taper the dose if discontinuation of therapy is considered.…”
Section: Ppi Pharmacology: What Is New and What Is Relevant To The CLmentioning
confidence: 95%